A Mixed‐Ligand Chiral Rhodium(II) Catalyst Enables the Enantioselective Total Synthesis of Piperarborenine B. Issue 16 (16th March 2016) - Panish, Robert A.; Chintala, Srinivasa R.; Fox, Joseph M.
Abstract: A novel, mixed‐ligand chiral rhodium(II) catalyst, Rh2 (S‐NTTL)3 (dCPA), has enabled the first enantioselective total synthesis of the natural product piperarborenine B. A crystal structure of Rh2 (S‐NTTL)3 (dCPA) reveals a "chiral crown" conformation with a bulky dicyclohexylphenyl acetate ligand and three N‐naphthalimido groups oriented on the same face of the catalyst. The natural product was prepared on large scale using rhodium‐catalyzed bicyclobutanation/ copper‐catalyzed homoconjugate addition chemistry in the key step. The route proceeds in ten steps with an 8 % overall yield and 92 % ee . Abstract : Mixing ligands : A new mixed‐ligand chiral rhodium(II) catalyst, Rh2 ( S ‐NTTL)3 (dCPA), has enabled the first enantioselective total synthesis of the natural product piperarborenine B. Key to the synthesis is a rhodium‐catalyzed bicyclobutanation/copper‐catalyzed homoconjugate addition for complex cyclobutane synthesis. The natural product was prepared on 400 mg scale and in 8 % overall yield.